Synergistically enhanced osteoconductivity and anti-inflammation of PLGA/beta-TCP/Mg(OH)(2) composite for orthopedic applications - Lee, Seul Ki; Han, Cheol-Min; Park, Wooram; Kim, Ik Hwan; Joung, Yoon Ki; Han, Dong Keun (Elsevier BV, 2019)
Synthetic biodegradable polymers including poly(lactide-co-glycolide) (PLGA) have been widely used as alternatives to metallic implantable materials in the orthopedic field due to their superior biocompatibility and biodegradability. However, weak mechanical properties of the biodegradable polymers and inflammatory reaction caused by the acidic degradation products have limited their biomedical applications. In this study, we have developed a PLGA composite containing beta-tricalcium phosphate (beta-TCP) and magnesium hydroxide (Mg (OH)(2)) as additives to improve mechanical, osteoconductivity, and anti-inflammation property of the biopolymer composite simultaneously. The beta-TCP has an osteoconductive effect and the Mg(OH)(2) has a pH neutralizing effect. The PLGA/inorganic composites were uniformly blended via a twin extrusion process. The mechanical property of the PLGA/beta-TCP/Mg(OH)(2) composite was improved compared to the pure PLGA. In particular, the addition of Mg(OH)(2) suppressed the inflammatory reaction of normal human osteoblast (NHOst) cells and also inhibited the differentiation of pre-osteoclastic cells into osteoclasts. Moreover, synergistically upregulated late osteogenic differentiation of NHOst cells was observed on the PLGA/beta-TCP/Mg(OH)(2) composite. Taken all together, we believe that the use of beta-TCP and Mg(OH)(2) as additives with synthetic biodegradable polymers has great potential by the synergistic effect in orthopedic applications.
Keywords: MECHANICAL-PROPERTIES; OSTEOGENIC DIFFERENTIATION; MAGNESIUM-HYDROXIDE; THERMAL-STABILITY; BONE; DEGRADATION; NANOPARTICLES; SCAFFOLDS; CELLS; ALLOY